The complete guide for SQL with Microsoft SQL server. (Packt Publishing, 2023)
Are you interested in learning SQL and database management? Our comprehensive course offers an in-depth look at the fundamentals of databases, including database types, SQL commands, table operations, and advanced concepts such as grouping sets and data types. In the first few sections, you will learn about data manipulation, including selecting, inserting, updating, and deleting data from a database. The course then dives into more advanced topics such as stored procedures, which allow you to write reusable code that can be executed multiple times. You will also learn about views, which provide a way to organize and simplify complex SQL queries, and triggers, which enable you to automate database actions based on certain events. The course then delves into transactions, which are essential for ensuring data consistency and reliability. You will also learn about normalization, which is the process of organizing data in a database to reduce redundancy and improve efficiency. The final sections of the course cover database backup and restore, as well as securing the database against potential threats such as SQL injection attacks. Throughout the course, you will gain hands-on experience by working with real-world examples and scenarios. By the end of the course, you will have a strong foundation in SQL and database management that will serve you well in any career that involves data management. What You Will Learn Understand the fundamentals of database design and management Learn to write SQL queries to extract and manipulate data Implement advanced SQL techniques such as subqueries and views Explore the different types of SQL triggers and transactions Create database backups and restore data in case of loss Secure your database against potential threats like SQL injections Audience This course is designed for anyone interested in learning SQL and database management, including beginners with little to no prior knowledge of SQL. It is suitable for individuals looking to gain skills for a career in data analysis, database administration, or software development. This course will also benefit professionals looking to enhance their current skill set with SQL knowledge. Students pursuing degrees in computer science, information technology, or related fields can also benefit from this course. About The Author Abhilash Nelson: Abhilash Nelson is a pioneering, talented, and security-oriented Android/iOS mobile and PHP/Python web application developer with more than 8 years of IT experience involving designing, implementing, integrating, testing, and supporting impactful web and mobile applications. He has a master's degree in computer science and engineering and has PHP/Python programming experience, which is an added advantage for server-based Android and iOS client applications. Abhilash is currently a senior solution architect managing projects from start to finish to ensure high quality and innovative and functional design.